Recent advances in g-C3N4 composites within four types of heterojunctions for photocatalytic CO2 reduction. Issue 14 (6th April 2021) - Que, Meidan; Cai, Weihua; Chen, Jin; Zhu, Liangliang; Yang, Yawei
Abstract : Photocatalytic CO2 reduction utilizes solar radiation as the main energy source to convert CO2 into clean chemical fuels, providing an alternative fuel for human production and life activities. Abstract : Studies of photocatalytic conversion of CO2 into hydrocarbon fuels, as a promising solution to alleviate global warming and energy issues, are booming in recent years. Researchers have focused their interest in developing g-C3 N4 composite photocatalysts with intriguing features of robust light harvesting ability, excellent catalysis, and stable performance. Four types of heterojunctions (type-II, Z-scheme, S-scheme and Schottky) of the g-C3 N4 composites are widely adopted. This review aims at presenting and comparing the photocatalytic mechanisms, characteristics, and performances of g-C3 N4 composites concerning these four types of heterojunctions. Besides, perspectives and undergoing efforts for further development of g-C3 N4 composite photocatalysts are discussed. This review would be helpful for researchers to gain a comprehensive understanding of the progress and future development trends of g-C3 N4 composite heterojunctions for photocatalytic CO2 reduction.